Casein kinase 1 promotes synchrony of the circadian clock network. - Zheng, X.; Sowcik, M.; Chen, D.; Sehgal, A. (Molecular and Cellular Biology, 2014)
Casein kinase 1, known as DOUBLETIME (DBT) in Drosophila melanogaster, is a critical component of the circadian clock that phosphorylates and promotes degradation of the PERIOD (PER) protein. However, other functions of DBT in circadian regulation are not clear, in part because severe reduction of dbt causes preadult lethality. Here we report the molecular and behavioral phenotype of a viable dbt(EY02910) loss-of-function mutant. We found that DBT protein levels are dramatically reduced in adult dbt(EY02910) flies, and the majority of mutant flies display arrhythmic behavior, with a few showing weak, long-period (?32 h) rhythms. Peak phosphorylation of PER is delayed, and both hyper- and hypophosphorylated forms of the PER and CLOCK proteins are present throughout the day. In addition, molecular oscillations of the circadian clock are dampened. In the central brain, PER and TIM expression is heterogeneous and decoupled in the canonical clock neurons of the dbt(EY02910) mutants. We also report an interaction between dbt and the signaling pathway involving pigment dispersing factor (PDF), a synchronizing peptide in the clock network. These data thus demonstrate that overall reduction of DBT causes long and arrhythmic behavior, and they reveal an unexpected role of DBT in promoting synchrony of the circadian clock network.